2019
DOI: 10.1088/1755-1315/365/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

What is kopi luwak? A literature review on production, quality and problems

Abstract: Kopi luwak or civet coffee is known as one of the most popular coffee in the world. This coffee produced from the finest and ripest coffee berries that are eaten by luwak (Paradoxorus hermaphroditus), a cat like-animal. Kopi luwak is currently recognized as the most special and most expensive coffee in the world. Kopi luwak production is initially done naturally by collecting kopi luwak from nature. However, due to the limited number, farmer began to cultivate kopi luwak with captivity (caged kopi luwak). A nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Luwak coffee is low in caffeine, low in fat, and low in bitterness. A study of different samples of civet coffee from the Gayo Highlands showed that nutty, fishy, chocolaty, herby, toasty, and earthy flavors were the dominant characteristics [ 3 ]. Coffea arabica berries are first digested by the Asian palm civet ( Paradoxurus hermaphroditus ), then the stools are either collected in the wild or harvested from caged animals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luwak coffee is low in caffeine, low in fat, and low in bitterness. A study of different samples of civet coffee from the Gayo Highlands showed that nutty, fishy, chocolaty, herby, toasty, and earthy flavors were the dominant characteristics [ 3 ]. Coffea arabica berries are first digested by the Asian palm civet ( Paradoxurus hermaphroditus ), then the stools are either collected in the wild or harvested from caged animals.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is the first and main producer of Luwak coffee; it became more popular in 2003 when Oprah Winfrey presented Luwak coffee in her TV show [ 3 ]. Luwak coffee can be produced naturally in the wild, or the animals can be kept in cages, which is referred to as captivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most popular coffee varieties are Coffea canephora L. (Robusta) and Coffea arabica L. (Arabika) (Skowron et al, 2020). As one of the expensive and popular coffees derived from those two varieties, Civet coffee (also known as Luwak coffee in Indonesia) is produced less than 127 kg per month, and the price ranges from USD 200-400 per kg, creating this a hundred times more costly than regular coffees (Muzaifa et al, 2019;Jumhawan et al, 2016). Currently, Indonesia has become the main producer of Luwak coffee, followed by East Timor, the Philippines, Thailand, Vietnam, and Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Oprah Winfrey Show and again in the 2007 film, "The Bucket List" starring Jack Nicholson and Morgan Freeman, kopi luwak is frequently cited as the most expensive coffee in the world due to its rare and unique production (Muzaifa et al, 2019). Yet with its fame came a shift towards caged farming (Shepherd, 2012).…”
mentioning
confidence: 99%